2014
DOI: 10.1177/0333102414534326
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between migraine and infant colic: A systematic review and meta-analysis

Abstract: In this meta-analysis, infant colic was associated with increased odds of migraine. If infant colic is a migrainous disorder, this would have important implications for treatment. The main limitation of this meta-analysis was the relatively small number of studies included.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 55 publications
0
26
0
4
Order By: Relevance
“…In a cross‐sectional study, mothers with migraine were more than twice as likely to have an infant with colic, pointing to the possible genetic relationship between infant colic and migraine . A recent meta‐analysis found the odds of migraine were increased if there was a history of infant colic (odds ratio 5.6 [95% confidence interval 3.3–9.5]) . A recent prospective cohort study done in Finland found that infant colic was associated with increased risk of migraine without aura by age 18 (relative risk 2.7 [95% confidence interval 1.5–4.7]), but not migraine with aura, again highlighting the possibilities that certain genes lead to specific phenotypes of migraine.…”
Section: Infant Colicmentioning
confidence: 99%
“…In a cross‐sectional study, mothers with migraine were more than twice as likely to have an infant with colic, pointing to the possible genetic relationship between infant colic and migraine . A recent meta‐analysis found the odds of migraine were increased if there was a history of infant colic (odds ratio 5.6 [95% confidence interval 3.3–9.5]) . A recent prospective cohort study done in Finland found that infant colic was associated with increased risk of migraine without aura by age 18 (relative risk 2.7 [95% confidence interval 1.5–4.7]), but not migraine with aura, again highlighting the possibilities that certain genes lead to specific phenotypes of migraine.…”
Section: Infant Colicmentioning
confidence: 99%
“…Bir araştırmada, infantil kolik öyküsü migrenli çocukların % 72.6'sında saptanırken, kontrol grubunun yalnız %26.5'inde bildirilmiştir (65) . Bir metaanalizde de infantil koliğin ileriki yaşamda migren riskini arttırdığı ileri sürülmektedir (66) . Sonuç olarak, infantil kolik yaşamın ilk 4 ayında bebeklerin %10-40'ında ortaya çıkan ağlama atakları olup, etiyolojisi tam olarak henüz aydınlatılamamış bir durumdur.…”
Section: Prognozunclassified
“…26 In a meta-analysis study, odds of migraine were increased five to six-fold if there was a history of infant colic (OR 5.6 (95% CI 3.3–9.5)). 27 In a prospective cohort study, “hyperreactivity” in early infancy, with crying being one of the factors incorporated into this concept, was a predictor of migraine in childhood. 28 Most convincingly, in a recent population-based prospective cohort study, infant colic was associated with increased risk of developing migraine without aura by age eighteen (RR 2.7 (95% CI 1.5–4.7)), but not migraine with aura, 29 suggesting that certain migraine genes might lead to specific clinical migraine phenotypes.…”
Section: The Case For Infant Colic As a Migrainous Phenomenonmentioning
confidence: 99%